2004
DOI: 10.1186/1472-6882-4-19
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal recipe versus diclofenac in symptomatic treatment of osteoarthritis of the knee: a randomized controlled trial [ISRCTN70292892]

Abstract: Background: Duhuo Jisheng Wan (DJW) is perhaps the best known and most widely used Chinese herbal recipe for arthralgia, but the clinical study to verify its efficacy is lacking. The purpose of this study was to compare the efficacy of DJW versus diclofenac in symptomatic treatment of osteoarthritis (OA) of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 14 publications
0
66
0
Order By: Relevance
“…An increasing number patients suffering from OA turn to complementary and alternative medicine treatments, including Chinese herbal medicine (14). Chinese herbal medicine, a major modality in traditional Chinese medicine (TCM) that has been practiced for thousands of years in China and other countries in Asia, has advanced in the treatment of OA, including improving clinical findings and inhibiting inflammatory reactions and cartilage degeneration (15,16). In vivo and in vitro studies have also indicated that Chinese herbal formulas produce multiple comprehensive effects against OA (17)(18)(19).…”
Section: Duhuo Jisheng Decoction-containing Serum Promotes Proliferatmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number patients suffering from OA turn to complementary and alternative medicine treatments, including Chinese herbal medicine (14). Chinese herbal medicine, a major modality in traditional Chinese medicine (TCM) that has been practiced for thousands of years in China and other countries in Asia, has advanced in the treatment of OA, including improving clinical findings and inhibiting inflammatory reactions and cartilage degeneration (15,16). In vivo and in vitro studies have also indicated that Chinese herbal formulas produce multiple comprehensive effects against OA (17)(18)(19).…”
Section: Duhuo Jisheng Decoction-containing Serum Promotes Proliferatmentioning
confidence: 99%
“…However, the percentages of S phase cells exhibited the opposite trend, and increased in a time-dependent manner. In the DHJSD 2-h serum group, the percentages of S phase cells were16.91±0.64, 22.28±2.45 and 28.05±2.63% following treatment for 24, 48 and 72 h, respectively. These were significantly higher than the corresponding percentages of the blank serum group (09.92±2.00, 17.02±2.96 and 24.20±1.05%, respectively; P<0.01 or P<0.05).…”
mentioning
confidence: 92%
“…In a 4-week double-blind RCT on knee OA, 3 g three times a day of Duhuo Jisheng Wan, a traditional Chinese cocktail of 15 plants, improved the LFI and multiple VAS of pain and stiffness as efficiently as 25 mg of diclofenac three times a day [129] (Table 4). Duhuo Jisheng Wan had a slower onset of action than diclofenac but an equal rate of adverse events, an observation that questions its safety.…”
Section: Resultsmentioning
confidence: 99%
“…Only two trials demonstrated efficacy when compared to an active comparator: NR-INF-02 (containing curcumin) 24 compared to glucosamine sulfate, 1,500 mg; and Harpadol ® (Devil's claw), containing Harpagophytum procumbens, compared to diacerein, 100 mg 77 (Figure 3). Two therapies demonstrated significantly worse efficacy than active control: a Chinese herbal recipe (Duhuo Jisheng Wan) over 4 weeks; 62 and willow bark extract (Salix daphnoides) over 42 days 63 of treatment. Both studies used the same active control (diclofenac, 75 mg/day or 100 mg/day) (Figure 4).…”
Section: Efficacymentioning
confidence: 99%
“…Botanical therapies that demonstrate efficacy when compared to an active comparator are olive oil 29 and UP446 28 (both low and high doses). Du huo ji sheng wan 62 and willow bark 63 favored the active comparator. There was no association between ES and risk of bias (ρ=0.2; P=0.…”
Section: Function Efficacymentioning
confidence: 99%